BS EN ISO 20236. Water quality. Determination of total organic carbon (TOC), dissolved organic carbon (DOC), total bound nitrogen (TN b) and dissolved bound nitrogen (DN b) after high temperature catalytic oxidative combustion. (29th August 2023) - British Standards Institution,
No abstract available